1970
DOI: 10.4314/sajas.v46i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micronized zeolite addition to lamb concentrate feeds on growth performance and some blood chemistry and metabolites

Abstract: This study was conducted to determine the effects of the addition of micronized zeolite (MZ) on the fattening performance, blood parameters, faecal ash and nitrogen levels of lambs fed concentrate feeds intensively. For two months 25 four-month-old Merino x Ile de France crossbred male lambs (21.1 ± 1.32 kg live weight) were fed 100 g alfalfa hay and a mixed concentrate diet containing 0%, 1%, 2% or 3% additional MZ. At the end of the study, bodyweight gain and feed consumption were not affected by the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
2
12
1
Order By: Relevance
“…Similarly, several studies have reported that CTL supplementation increased the daily feed intake of livestock [ 13 , 40 , 41 ]. Otherwise, the lambs’ weight gain in our experiment was not affected by CTL supplementation, while in other studies, dietary supplementation with CTL has been proven to increase weight gain in lambs [ 18 , 40 , 41 ]. This lack of effect on the weight gain of the lambs might be due to the limited sample size used in our study.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Similarly, several studies have reported that CTL supplementation increased the daily feed intake of livestock [ 13 , 40 , 41 ]. Otherwise, the lambs’ weight gain in our experiment was not affected by CTL supplementation, while in other studies, dietary supplementation with CTL has been proven to increase weight gain in lambs [ 18 , 40 , 41 ]. This lack of effect on the weight gain of the lambs might be due to the limited sample size used in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Similarly, other studies have reported that CTL supplementation enhances weight gain (carcass characteristics were not evaluated) [ 17 , 41 , 42 ]. The effects of CTL supplementation in lambs in other studies, could be related to the ability of CTL to modify ruminal fermentation due to its cation exchange property, resulting in better energy efficiency by improving the acetate:propionate ratio or by stimulating some populations of ruminal bacteria [ 18 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Toprak et al (2016) found that average daily gain and weights at slaughter did not affected in lambs fed diets containing 0, 1%, 2% and 3% zeolite.…”
Section: Lambs Body Weightmentioning
confidence: 87%
“…Zeolites dietary supplementation is a cooperative and efficacious strategy in the prevention of several diseases and in the advancement of animal health. Many authors in several species, such as swine [128], calves [129], and lambs [130], have documented the benefits of their dietary inclusion. Briefly, below some mechanisms by which zeolite minerals may exert their performance-promoting properties in the diet of livestock husbandry [131]:…”
Section: Animal Feed Additivementioning
confidence: 99%